A socio-legal research on personal data protection and privacy practices of Malaysian organisations - Abdul Ghani, A.S. (2006)
This paper describes a qualitative research that was conducted as part of a PhD research on online privacy and the law. The research was conducted on selected public and private organisations in Malaysia that collect and/or process personal data online. The method used is multi-case study and the data are collected by semi-structured interviews. The data are analysed with the aid of a computer assisted qualitative data analysis software (or CAQDAS). This paper will also describe the socto-teqal' significance of this qualitative research as well as lessons learned from conducting the study